A biosensor approach to probe the structure and function of the adsorbed proteins: fibrinogen at the gold surface - Snopok, B.A.; Kostyukevych, K.V.; Rengevych, O.V.; Shirshov, Yu.M.; Venger, E.F.; Kolesnikova, I.N.; Lugovskoi, E.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
The kinetics of adsorption and surface structure of adsorbed layers of the human fibrinogen on the gold surface, determined by Surface Plasmon Resonance (SPR) and Atomic Force Microscopy (AFM) analysis, was employed to probe the lateral distribution and preferred orientation of protein molecules within the monolayer. In this study, special sets of immunoassays are presented for fibrinogen adsorption/conformation analysis. The results show that kinetic parameters of antigen-antibody interactions are directly related to the interfacial conformation of fibrinogen molecules. Various interfacial structures of adsorbed fibrinogen aggregates, namely single, bi- and three- molecular aggregates, were obtained using a combination of AFM imaging and SPR analysis. Adsorption of fibrinogen onto the surface of polycrystalline gold is a complex process including surface-induced unfolding, local self-assembly and adsorption, occurring concurrently with – and on the time scale of – each other. This result confirmed the utility of the proposed approach for detecting the spatial distribution and biofunctional properties of specific proteins adsorbed from biological liquids in biosensors. Просторовий розподіл та переважна орієнтація молекул білків у моношарі досліджена з застосуванням кінетики поверхневого плазмонного резонансу (ППР) та мікроскопії атомних сил (МАС) підчас адсорбції фібріногену людини на поверхню золота. У роботі проведена серія специфічних імунних реакцій щоб проаналізувати адсорбційно-конформаційний стан плівок фібріногену. Отримані результати демонструють прямий звўязок кінетичних параметрів реакції антиген-антитіло з конформацією фібріногену на межі розподілу. Застосування МАС і ППР аналізів дало можливість визначити одно-, двух- та трьох молекулярні структурні сполуки фібріногену на межі розподілу. Адсорбція фібріногену на поверхню полікрісталічного золота - це складний процес, що містить: розгортання, стимульоване поверхнею, само-збирання та адсорбцію, які відбуваються конкурентно у часі. Цей результат підтверджує перспективу запропонованого підходу у біосенсорній техніці для визначення просторового розподілу та біофункціональних властивостей специфічних білків, які адсорбуються з біологічних рідин. Пространственное распределение и преимущественная ориентация молекул белков в монослое изучена с использованием кинетики поверхностного плазмонного резонанса (ППР) и микроскопии атомных сил (МАС) при адсорбции фибриногена человека на поверхность золота. В работе проведена серия специфических имунных реакций для адсорбционо-конформационного анализа пленок фибриногена. Полученные результаты демонстрируют прямую связь кинетических параметров реакции антиген-антитело с конформацией фибриногена на границе раздела. Применение МАК и ППР анализов позволило определить одно-, двух и трех-молекулярные сочетания фибриногена на границе раздела. Адсорбция фибриногена на поверхность поликристаллического золота является сложным процессом, включающим, разворачивание, стимулируемое поверхностью, само-сборку и адсорбцию, происходящим конкурентно во времени. Этот результат подтверждает перспективу предлагаемого подхода в биосенсорной технике для определения пространственного распределения и биофункциональных свойств специфических белков, адсорбируемых из биологических жидкостей.